Investigación y docencia en el Instituto Nacional de Ciencias de la JAE - Gomis Blanco, Alberto (Revista Complutense de Educación, 2007)
By Royal Decree, on 27 May 1910 the Junta para Ampliación de Estudios joined at the Instituto Nacional de Ciencias Físico-Naturales several Museums and Laboratories previously existing that were devoted to those sciences by means of laboratory research, courses, printed books and articles, fieldwork, etc. Renamed Instituto Nacional de Ciencias by Royal Decree on 23 December 1916, two new institutions will arise from it: the Instituto Nacional de Física y Química (in September 1931) and the Instituto Nacional de Ciencias Naturales (in September 1936, once the civil war han broken). Along those nearly three decades the Instituto Nacional de Ciencias constituted a significant progress both in the scientific research and the teaching developed in every one of its dependencies, as it is meant to be shown through this paper.